World University Presidents Summit reflections on diversity and harmonization, 3rd FISU Rector Forum 2006, 19-22 July 2006, Queen Sirikit National Convention Center, Bangkok - World University Presidents Summit (2006 Bangkok); International University Sports Federation. Rector Forum 2006 Bangkok). ([Bangkok] produced by Media Active, 2006)
This is an invitation for Heads/CEOs of national, regional and international associations of universities, CEOs from the corporate world interested and involved in higher education, Presidents, Vice-Chancellors and Rectors of Universities from around the World, High ranking Officers of National Ministries of Education and related departments, Representatives of UNESCO, World Bank, OECD, EU and other international multi-lateral agencies, Senior Leaders and researchers from independent think tanks and research institutes to share views, experiences, innovations and collaborative ideas.
Keywords: College presidents -- Congresses; Universities and colleges -- Congresses; Education, Higher -- Congresses